2016
DOI: 10.1002/app.43902
|View full text |Cite
|
Sign up to set email alerts
|

Thermoplastic rubber/PP elastomers toward extremely low thermal expansion

Abstract: Fine regulation of the microstructure of rubber/polypropylene (PP) alloys could remarkably reduce the coefficient of linear thermal expansion (CLTE) while retaining the mechanical properties similar to those of thermoplastic elastomers. Rubber/PP elastomers with different morphologies were successfully prepared by controlling the appropriate rubber type, viscosity ratio, and processing method. The CLTE of the polymer alloy parallel to the microlayer directions was considerably reduced when the rubber domains w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Unlike these other actuators, Chen et al demonstrated a highly pH‐sensitive SMP with a functionality independent of heat . Demonstrated pH‐responsive SMPs in general, however, tend to be especially slow, and work is in progress to improve the response times from the scale of hours to minutes …”
Section: Chemically Responsive Soft Actuatorsmentioning
confidence: 99%
“…Unlike these other actuators, Chen et al demonstrated a highly pH‐sensitive SMP with a functionality independent of heat . Demonstrated pH‐responsive SMPs in general, however, tend to be especially slow, and work is in progress to improve the response times from the scale of hours to minutes …”
Section: Chemically Responsive Soft Actuatorsmentioning
confidence: 99%
“…[ 9–11 ] One of these forms is the blending of thermoplastic elastomers (TPE) to polypropylene, the first having low elastic modulus, high elongation, good impact toughness, and compatibility with polyolefins depending on their chemical structure. [ 12–19 ]…”
Section: Introductionmentioning
confidence: 99%
“…In the previous studies in our group, we found that the polycarbonate polyurethane (PCPU) exhibits excellent water resistance, heat resistance, and weatherability. [53][54][55][56] Here, we prepared two layers of coating coated mesh with superhydrophilicity and underwater superoleophobicity. First, we synthesized inner layer that PCPU with terminal group of C]C and then coated it onto the stainless steel mesh (PCPU-coated mesh).…”
Section: Introductionmentioning
confidence: 99%